“But man is not made for defeat”: insights into Ernest Hemingway’s dementia - Léo Coutinho; Hélio Afonso Ghizoni Teive (Arquivos de Neuro-Psiquiatria)
ABSTRACT Ernest Hemingway is widely regarded as one of the greatest fiction writers of all time. During his life, he demonstrated several signs of psychological suffering with gradual worsening and presentation of cognitive issues over his late years. Some of his symptoms and the course of his disease suggest that he might have suffered from an organic neurodegenerative condition that contributed to his decline, which culminated in his suicide in 1961. In this historical note, we discuss diagnostic hypotheses compatible with Hemingway’s illness, in light of biographical reports.